Coordination in Large-Scale Software Development: Helpful and Unhelpful Behaviors - Begel, Andrew; Nagappan, Nachi (Microsoft Research, 2009)
Large-scale software development requires coordination within and between very large engineering teams which may be located in different buildings, on different company campuses, and in different time zones. At Microsoft Corporation, we studied a 3-year-old, 300-person software application team based in Redmond, WA to learn how they coordinate with three intra-organization, physically distributed dependencies: a platform library team also in Redmond; a team three time zones away in Boston, MA; and a team in Hyderabad, India. Thirty-one interviews with 26 team members revealed that coordination was most impacted by issues of communication, capacity and cooperation. Distributed teams faced additional challenges due to time zone and cultural differences between the team members. We support our findings with a survey of 775 engineers across Microsoft who described their experiences managing coordination in their own software products. We suggest new processes and tools to improve team coordination.